NetCDF mean underwater glider data collected in the Northern Benguela during February - June 2018. Part 2: optical backscattering and fluorescence data - Lovecchio, Elisa; Henson, Stephanie A; Carvalho, Filipa; Briggs, Nathan; Hilder, Hans (PANGAEA, 2025)
Binned mean optical data of Slocum G2 glider data from the surface to 1000 m depth collected between 14 February – 19 June 2018 in the northern Benguela upwelling system around -18.14 N, 10.91 E. Glider bio-optical data was collected using a Seabird WETLabs ECO-puck BB2FL measuring optical backscattering at 700 nm and chlorophyll fluorescence at around 20 cm vertical resolution. Full-resolution backscattering data were partitioned into a small particle fraction (refsmall variable) and a large particle fraction (spikes variable) following the methods of Henson et al. (2023, doi:10.1016/j.dsr2.2023.105274), adapted from Briggs et al. (2011). The same method was applied to chlorophyll fluorescence to identify highly fluorescent spikes in the signal. The glider data (both partitioned and non partitioned, i.e. combined signal) were then binned into 6 hourly, 2 m depth bins. This data originates from the same glider of the data published here: https://doi.pangaea.de/10.1594/PANGAEA.938221 A full description of the glider mission and binned glider data for temperature, salinity and oxygen can be found at the above link.
Keywords: Backscatter; Benguela; Benguela Upwelling System; Fluorescence; Glider; Namibia; ocean; spikes